Philosophy of medicine - University of Pittsburgh. University Library System (University Library System, University of Pittsburgh, 2020)
"Philosophy of Medicine is an open-access journal that publishes exceptional original philosophical research and perspectives on all aspects of medicine, including medical research and practices."
Keywords: Medicine : Philosophy : Periodicals; Medicine : Philosophy